2014
DOI: 10.1017/s0950268814002258
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and persistent infection of high-risk human papillomavirus

Abstract: Alcohol consumption is a possible co-factor of high-risk human papillomavirus (HR-HPV) persistence, a major step in cervical carcinogenesis, but the association between alcohol and continuous HPV infection remains unclear. This prospective study identified the association between alcohol consumption and HR-HPV persistence. Overall, 9230 women who underwent screening during 2002-2011 at the National Cancer Center, Korea were analysed in multivariate logistic regression. Current drinkers [odds ratio (OR) 2·49, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 38 publications
2
18
0
1
Order By: Relevance
“…The percent of women consuming alcohol during pregnancy has been reported as a serious problem in other countries, such as 32.5% in Congo [ 31 ], 4.4% in India [ 32 ]. A study in Korea [ 33 ] suggests that women who drink alcohol may have an increased risk of persistent HPV. They tested 9230 women for HPV and found that current drinkers were nearly three times more likely than non-drinkers to test positive for HPV at the beginning of the study, and then again at a 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The percent of women consuming alcohol during pregnancy has been reported as a serious problem in other countries, such as 32.5% in Congo [ 31 ], 4.4% in India [ 32 ]. A study in Korea [ 33 ] suggests that women who drink alcohol may have an increased risk of persistent HPV. They tested 9230 women for HPV and found that current drinkers were nearly three times more likely than non-drinkers to test positive for HPV at the beginning of the study, and then again at a 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…High parity, early age at first pregnancy, heredity, excessive sex and alcohol/drug were less frequently cited by the women. High parity and early age at first pregnancy have been described in the literature as risk factors for cervical cancer [ 17 , 19 ]; however, the role of heredity and alcohol/drug use remains unclear [ 17 , 20 ]. A high proportion of women (62.3%) reported that they were moderately/extremely worried about having/developing cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…High-risk Human Papillomavirus (HR-HPV) persistence has been confirmed as a major step in cervical carcinogenesis. Prospective studies showed that alcohol consumption was associated with increased risks of cervical HR-HPV persistence [ 48 , 49 ]. Alcohol drinkers also showed higher risks of cervical intraepithelial neoplasia (CIN) 1 compared with abstainers, and high drinking frequency and quantity would even aggravate the issue [ 50 ].…”
Section: Cancermentioning
confidence: 99%